PENGARUH VIDEO ANIMASI BING TERHADAP KEMAMPUAN MENYIMAK ANAK KELOMPOK B DI TK TUNAS HARAPAN NAGARI TIGO KOTO SILUNGKANG KABUPATEN AGAM - Adela, Adela Fitri; Rismareni Pransiska; Farida Mayar, Zulminiati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aimed to determine if Group B students at Tunas Harapan Kindergarten in Nagari Tigo Koto Silungkang, Agam Regency, were able to improve their listening skills after seeing Bing cartoon films.  This study employed a one-group pretest-posttest design based on quantitative research methods. It was a pre-experimental approach.  Thirteen students served as the research sample, with all students at Tunas Harapan Kindergarten making up the study population.  A hypothesis test, homogeneity test, and normalcy test were employed for the data analysis.  A paired sample test was used to evaluate the hypothesis.  The data was subsequently processed using the Windows application SPSS 26.  After treatment, the total score increased from 233 (average score: 17.92) to 341 (average score: 26.23).  Group B students at Tunas Harapan Kindergarten in Nagari Tigo Koto Silungkang, Agam Regency, had their listening skills affected by Bing animated films, according to the study's conclusions.  The researcher's hypothesis test yielded a sig value (2-tailed) of 000 < 0.05, thereby rejecting H0 and accepting Ha.